2006
DOI: 10.1111/j.1365-2125.2006.02752.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of darbepoetin alfa in healthy subjects

Abstract: AimTo develop and evaluate a population pharmacokinetic (PK) model of the long-acting erythropoiesis-stimulating protein, darbepoetin alfa in healthy subjects. MethodsPK profiles were obtained from 140 healthy subjects receiving single intravenous and/or single or multiple subcutaneous doses of darbepoetin alfa (0.75-8.0 µ g kg − 1 , or either 80 or 500 µ g). Data were analysed by a nonlinear mixed-effects modelling approach using NONMEM software. Influential covariates were identified by covariate analysis em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
16
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
10
16
1
Order By: Relevance
“…We explain our contradictory results by: first the difference in the age of the animals in (A) and (B), and second, the interanimal and/or occasion variabilities. Because the body weight is accounted for in our PK parameters, the correlation between body weight and EPO clearance that was previously established [25,26] may not be considered as an influence factor to explain our observed differences.…”
Section: Pharmacokineticscontrasting
confidence: 46%
“…We explain our contradictory results by: first the difference in the age of the animals in (A) and (B), and second, the interanimal and/or occasion variabilities. Because the body weight is accounted for in our PK parameters, the correlation between body weight and EPO clearance that was previously established [25,26] may not be considered as an influence factor to explain our observed differences.…”
Section: Pharmacokineticscontrasting
confidence: 46%
“…A majority of the adult pharmacokinetic studies pooled data from patients who received darbepoetin alfa intravenously and via subcutaneous injection [3436]. These studies used a two-compartment model to describe darbepoetin alfa pharmacokinetics [3436].…”
Section: Discussionmentioning
confidence: 99%
“…In adults, Darbe demonstrated even slower absorption, reaching its peak at around 54.1 h after s.c. administration 3 . The absorption rate constant of Darbe in infants following s.c. administration estimated using our model was 0.062 L/h, and the absorption half-life was 11.2 h. The absorption rate constant of Darbe (ka) in adults was reported to be 0.0212 L/h, 17 corresponding to an absorption half-life of 32.7 h. The higher ka value and shorter absorption half-life in infants reflect a much faster absorption process than in adults, which is consistent with the observed data. The lymphatic system represents a major route for the absorption of protein drugs, including Epo 18 , 19 .…”
Section: Discussionmentioning
confidence: 86%
“…Agoram et al 17 performed population pharmacokinetic analysis to characterize Darbe disposition in healthy adults and reported that Darbe pharmacokinetics in adults was well described by a 2-compartment model, with clearance equal to 0.00234 L/h/kg and volume of distribution of central compartment equal to 0.085 L/kg. However, in contrast to the pharmacokinetic parameters in adults, our study revealed a clearance of Darbe in infants that is much more rapid (0.05 L/h/kg, in male infants, and 0.031 L/h/kg in female infants) and that the volume of distribution is much greater (0.84 L/kg).…”
Section: Discussionmentioning
confidence: 99%